2005
DOI: 10.1021/ef0498770
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Interaction Energy of Asphaltene Aggregates with Aromatic Solvents

Abstract: The molecular interactions between asphaltenes and solvents are an important parameter that dominates the processing behavior of asphaltenes. This study has developed a method for estimating the interaction energy of asphaltene (or resin) aggregates with aromatic solvent molecules. The thermal properties of three asphaltenes and one resin have been ascertained using differential scanning calorimetry (DSC) and thermogravimetry analysis (TGA), and the heats of solution (∆H solu ) of the two species in quinoline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…24,25 In many cases, the models were successfully fit to the behavior of the mixtures. Solubility parameters have proven to be advantageous in averaging the properties of a solvent + an anti-solvent, e.g., heptane + toluene mixtures, once one or more additional fitting parameters are introduced.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24,25 In many cases, the models were successfully fit to the behavior of the mixtures. Solubility parameters have proven to be advantageous in averaging the properties of a solvent + an anti-solvent, e.g., heptane + toluene mixtures, once one or more additional fitting parameters are introduced.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Extensive characterization of the aggregation behavior of these asphaltene samples has been reported previously, using small-angle neutron scattering measurements (SANS) , molecular dynamics simulation , small-angle x-ray scattering (SAXS) (Tanaka et al, 2004), differential scanning calorimetry (Zhang et al, 2005), and molecular-weight distribution analysis . The kinetic observations from the present study may be correlated to some aspects of the aggregation behavior, for example, SAXS analysis showed that the Khafji asphaltenes disaggregated at 179 • C, compared to 241 • C for Maya and 243 • C for Iranian Light.…”
Section: Selectivitymentioning
confidence: 99%
“…Typically, resin and asphaltene molecules tend to form association structures, which lead to crude oils with very high viscosity [14][15][16] . The major forces governing the resin and asphaltene aggregates formation are very complicated, including charge transfer, electrostatic interaction, van der Waals force, the acid-base interaction, hydrogen bonding, π -π interaction and coordination interaction [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%